STRATEGI PEMASARAN DAN PENGEMBANGAN BISNIS ONLINE (STUDI KASUS KEDIRI) - Dewi Wungkus Antasari (REVITALISASI : Jurnal Ilmu Manajemen, 2019)
Online Bussiness is a media that have possibility for consumen to buy goods and service from the seller directly by using internet browser media. This online transaction process also known as e-commerce. Online bussiness in Kediri have become an often phenomena because it has a lot of benefit and advantage, not only for the seller but also for the consumen. The seller has to have the specific strategy to market and to develop their bussiness in order to make it continue. And also make a good solution of some obstacle that they get.This research is aimed to the